ButterSweet Bakery / Muhammad Sadiq Iskandar Rahmat ... [et al.] - Rahmat, Muhammad Sadiq Iskandar; Azizan, Nur Fatihah Izazi; Norazam, Nurul Fatihah; Ishak, Syaznirah; Shahrim Al-Amin, Shafiqah Nur Ain (2021)
Butter Sweet Bakery is located at Jalan Gunung Rapat2, Jalan Gopeng, Ampang, 31350 Ipoh Perak. This bakery will be offered and serve you a high-quality bakery to all our customers in Ipoh Perak. Throughout the working day, our bakery will provide freshly baked cake, pastry, cookies and many more. Throughout the business day, six to eight reasonable batches of cakes and pastry products are cooked to ensure that fresh baked foods are constantly accessible. This bakery can obviously be classified as a quick-service dessert establishment, since clients will receive their cakes as quickly as possible after placing their orders. In Ipoh Perak there are a few famous and well-known bakeries. Butter Sweet Bakery was intending to establish a strong market position there. We are also trying to provide clients with the best and most cheap prices while providing high-quality bakeries. It is because we are attempting to satisfy the need of the income local market in the residents in Ipoh Perak as well as the tourist at a competitive price. Moreover, this Butter Sweet Bakery was created with the cooperation of the 5 friends. We are building this business to gain more knowledge about business. After we received a good reaction to our regular customers, so we are decided to build this business to a large scale